Implementasi Kebijakan “Mappadeceng” Dalam Bidang Pendidikan di Kabupaten Soppeng - Tri Cahyo Nugroho; Suriadi Lambali; Hamsina Hamsina (Department of Public Administration, Muhammadiyah University of Makassar, 2023)
This study aims to analyze the implementation of the